09 Biomarkers for Detection of Activated Macrophages in Atherosclerosis. (20th November 2012) - Bird, JLE; Burzynski, L; Manavaki, R; Rudd, JHF; Warburton, EA; Davenport, AP
Abstract : Atherosclerosis is the pathogenic mechanism underlying the majority of strokes, heart attacks and peripheral vascular disease. These are the principal causes of morbidity and mortality in the developed nations. The atherosclerotic lesion (or plaque) is characterised by a build up of lipid and inflammatory cells in the artery wall. Arterial stenosis is the current clinical predictor for endarterectomy, although macrophage burden in the lesion correlates strongly with likelihood of rupture and could be a better proxy of plaque vulnerability. Activated macrophages have up-regulated expression of translocator protein (TSPO), which is readily quantified by the positron emission tomography (PET)-based ligands (1) such as [11C](R)-1-(2-chlorophenyl)-N-methyl-N-(1-methylpropyl)-3-isoquinoline-carboxamide ([11C](R)-PK11195). Studies examining TSPO plaque biodistribution frequently use CD68, a pan-phenotype marker, for identification of macrophage presence. However, this biomarker demonstrates some inconsistencies in these analyses (1). We hypothesise that more specific macrophage phenotype markers may perform better as correlates for TSPO PET-ligand binding. In this study, we examined the expression of phenotype-restricted macrophage markers in endarterectomy tissue, and correlated these with the distribution of [3H](R)-PK11195 using autoradiographic, immunohistochemical and immunofluorescence techniques. Autoradiographic and immunohistochemical images were digitised and co-registered to provide more accurate correlation of expression. We identified several markers of activated macrophage phenotype which have better correlation with [3H](R)-PK11195 binding patterns compared with CD68. These data indicate that TSPO PET ligands bind principally to activated macrophage phenotypes, and the phenotype markers have the potential to more accurately identify PET-ligand binding macrophages in ex vivo analysis. 1) Bird JL et al. Atherosclerosis, (2010), 210(2): 388–91.